2002
DOI: 10.1159/000047925
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Matrix Production and Lamellar Bone Formation of Human Osteoblast-Like Cells in Porous Titanium Implants

Abstract: The goal of this study was to characterize growth, mineralization and bone formation of osteoblast-like cells in titanium pore channels of defined diameter. Titanium implants with continuous drill channels of diameters of 300, 400, 500, 600 and 1,000 µm were inserted into human osteoblast-like cell cultures. The ingrowth of the cells into the drill channels was investigated by transmitted-light microscopy and scanning electron microscopy. Immunofluorescence and histological analysis of 15-channel sections of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 36 publications
6
49
0
Order By: Relevance
“…Several studies have demonstrated these properties either with osteoblast cultures 5,20 or with in vivo experiments 3,4,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated these properties either with osteoblast cultures 5,20 or with in vivo experiments 3,4,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to obtain osseointegration, the surgical cavity must be prepared with the least injury possible [15,50,58]. In order to cause minimal damage to the surrounding bone tissues, in the present study, bone perforation was performed using burs of increasingly larger diameters, and under constant saline irrigation.…”
Section: Histological Evaluation Of Ti Implant Samplesmentioning
confidence: 99%
“…Furthermore, it may influence the early formation of fibrin clots, platelet activation and the production of growth factors related to bone tissue, thereby interfering directly in cell recruitment, adhesion, proliferation and differentiation [24]. Evidence suggests that the mechanism by which the topography of Ti influences the differentiation of osteoblasts is related to the pathways of phospholipase A2, protein kinase A and integrin.…”
Section: Biomimetic Treatmentmentioning
confidence: 99%
“…Numerous studies have shown that implant porosity promotes positive results in bone neoformation in vivo [4,5,[8][9][10]22,23], since it increases the contact area between the biomaterials and bone tissue [4,22], resulting in improved implant stability over time, as well as accelerating the process of osseointegration [24]. Concomitantly, various studies have shown that the implant surface can alter the metabolism and phenotypic expression of osteoblastic cells [22,23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation